DENSITAS SPIKULA ANGGOTA HOLOTHUROIDEA SEBAGAI AGEN BIOASESMEN PENCEMARAN MERKURI DI LAMPON KABUPATEN BANYUWANGI - Susintowati; Baiturohman , Moh.; Nugrahani , Magdalena Putri (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
Exploration of the effects of mercury pollution in the Lampon estuary is still necessary, after there were indications of impacts on several bioindicator species. This study used spicule density of members of the order Holothuroidea as a bioassessment agent for the pollutant. Data collection on Holothuroidea populations was carried out using a quantitative descriptive method, using transects and 4 m2 quadrat plots. The species diversity index was analyzed using the Shannon-Weinner index. The main data collection locations were at the Lampon estuary and the rocky coast of Lampon, while control data was taken from the rocky coast of Rajegwesi, Merubetiri National Park. Spicule density was obtained by maceration of specimen tentacle organs, then spicules were observed and counted using a binocular microscope. The environmental parameters measured were water temperature, sediment temperature, water pH, water salinity, and dissolved oxygen (DO) in the water. The results showed that the diversity index of each study location was relatively low; the diversity index in Lampon was 0,838 and the diversity index in Rajegwesi was 0,826. A one-way ANOVA analysis showed no significant difference in spicule density in Holothuria leucospilota, but there was a significant difference in spicule density in Leucosynapta sp. at both locations. The suspected effects of mercury pollution on members of the Holothuroidea still require further investigation, although spicule density can be used as an agen of bioassessment.